Update on Thin Melanoma: Outcome of an International Workshop. (January 2016) - Mihic-Probst, Daniela; Shea, Chris; Duncan, Lyn; de la Fouchardiere, Arnaud; Landman, Gilles; Landsberg, Jennifer; ven den Oord, Joost; Lowe, Lori; Cook, Martin G.; Jung Yun, Sook; Clarke, Loren; Messina, Jane; et al.
Abstract : The following communication summarizes the proceedings of a 1-day Workshop of the International Melanoma Pathology Study Group, which was devoted to thin melanoma. The definitions and histologic criteria for thin melanoma were reviewed. The principal differential diagnostic problems mentioned included the distinction of thin melanoma from nevi, especially from nevi of special site, irritated nevi, inflamed and regressing nevi, and dysplastic nevi. Histologic criteria for this analysis were discussed and the importance of clinico-pathologic correlation, especially in acral sites, was emphasized. Criteria for the minimal definition of invasion were also discussed. In addition, a new technique of m-RNA expression profiling with 14 genes was presented and facilitated the distinction of thin melanomas from nevus in histologically obvious cases. However, for particular nevi, it was not obvious why the results indicated a malignant lesion. Despite many molecular and other ancillary investigations, Breslow thickness remains the most important prognostic factor in thin melanoma. The prognostic significance of radial (horizontal) and vertical growth phases, Clark level, regression, and mitotic rate were also discussed. Because of the increasing frequency of thin melanomas, there is a great need to develop more refined predictors of thin melanomas with worse clinical outcome.